The Causes and Effects of Crimes by a Psychopathic Prisoner Suffering from Narcissistic Personality Disorder and Terry's Struggle to Againts It in Sam Miller’s Film “No Good Deed” - Violet, Miora Libyatta; Ramadhina, Retno; Priyoto, Priyoto (STIBA IEC JAKARTA, 2024)
The objectives of this research are: (1.)To find out what is narcissistic personality disorder in the movie no good deed. (2.) To find out how Terry struggle against to save her life from Psychopathic Prisoners that has Narcissistic Personality Disorder. (3.) to analyse the causes and effect of the crimes committed by Colin who has Narcissistic Personality Disorder. This research was conducted using a qualitative method because the writer focuses on psychological understanding of the characters and social phenomena that occur in the film. This aims to gain a deep understanding, and develop the theories contained in the film. To achieve this objective, the writer uses two approaches, namely Psychological Approach and Sociological Approach..